Improving Collaboration Skills, Critical Thinking, and Science Learning Achievement in Grade VII through Discovery Learning with TarL Approach - Rahmawati, Laifa; Aji, Latief Susila; Sari, Hasna Irfantiningtyas; Prasetio, Hadi Eko; Ningsih, Fuji Hutami; Harlena, Ismi Dian Khairunnisa; Laila, Fadhilah Nur; Sari, Feby Permata; Maryanto, Allesius (Journal of Classroom Action Research, 2025)
Collaboration skills, critical thinking skills, and learning achievement are important for every student to have. However, the results of the researcher's observation in class VII D SMP N 4 Depok showed that collaboration skills, critical thinking, and science learning achievement were still low. Therefore, this study aims to analyze the improvement of collaboration skills, critical thinking skills, and learning achievement of students in class VII D SMP N 4 Depok after learning the Discovery Learning model with TarL approach on Earth and Solar System material. This research is a classroom action research (PTK) model of Kemmis & Mc Taggart with two cycles consisting of four stages, namely planning, action, observation, and reflection in each cycle. The subjects in this study were students of class VII D SMP N 4 Depok. Data collection techniques used observation, questionnaires, tests, and documentation. Data analysis of questionnaire and test results used descriptive statistics and n-gain test. The results obtained showed that there was an increase in cycle 1 to cycle 2 in the medium category, namely 1) collaboration skills with N Gain 0.413; 2) critical thinking skills with N Gain 0.413. Critical thinking ability with N Gain 0.474; 3) Learning achievement with N Gain 0.532. Thus, the application of Discovery Learning with TarL Approach is effective to improve collaboration skills, critical thinking skills, and learning achievement.